Giacomo Puccini: A Discography - Flury, Roger (Rowman & Littlefield Publishers, 2012)
Opera recordings have been with us since the creation of the first wax cylinders. Now at a time when the 25-year reign of the compact disc appears to be coming to an end is the moment to take stock of the history of recordings of arguably the most popular composer of operas, Giacomo Puccini. In Giacomo Puccini: A Discography, librarian and music historian Roger Flury looks at each opera chronologically from Le Villi to Turandot, followed by sections on Puccini's instrumental, chamber, orchestral, and solo vocal works. Details of each complete opera are listed by recording date, followed by excerpts in the order in which they occur in the opera. Recordings of each aria are listed alphabetically by the name of the artist. For ease of use, Flury establishes as the main criteria for inclusion those recordings assigned a commercial issue number and available for purchase. This book does not limit itself to mainstream recordings but includes as well 'unofficial' recordings taken from broadcasts or illegally recorded in theaters, ensuring that the audio recording history of Puccini is free of gaps. (Video and DVD issues, whether of staged performances or excerpts in concert, are not included unless they have been issued in a sound-only format.) This volume brings together information on nearly 10,000 recordings of Puccini's music. It provides a comprehensive overview of the recorded history of the composer's works and serves as a useful guide for the transfer of recordings from one format to another.